The influence of rituximab, high-dose therapy followed by autologous stem cell transplantation, and age in patients with primary CNS lymphoma - Madle, Michael; Krämer, Ines; Giesen, Nicola; Schwarzbich, Mark-Alexander; Wuchter, Patrick; Herfarth, Klaus; Egerer, Gerlinde; Ho, Anthony Dick; Witzens-Harig, Mathias (Annals of hematology, 2015)
For patients with diffuse large B cell lymphoma without the involvement of the CNS, the addition of rituximab to standard chemotherapy has significantly improved survival. In this single-center, retrospective analysis, a total of 81 primary CNS lymphoma (PCNSL) patients treated in our institution between 2000 and 2011 were included. Beside first-line chemotherapy with or without rituximab, we evaluated the impact of age (≤/>60 years), autologous stem cell transplantation (ASCT +/−), and other factors upon overall survival (OS) and progression-free survival (PFS). In patients treated with rituximab (n = 27), 3-year OS was 77.8 % (95 % confidence interval (CI) 62-93 %). In contrast, in patients treated without rituximab (n = 52), 3-year OS was only 39.9 % (CI 27-53 %, Fig. 1). The difference in OS was significant in the univariate (p = 0.002) as well as in the multivariate analysis (p = 0.049, hazard ratio (HR) = 0.248). Patients ≤60 years of age (n = 28) had a 3-year OS of 78.2 % (CI 63-94 %); in patients >60 years (n = 51), 3-year OS was 38.7 % (CI 25-52 %). Patients who received high-dose therapy and ASCT had a 3-year OS of 85.2 % (CI 72-99 %), and 65.1 % were alive up to the time of analysis (range 9-131 months). Without ASCT, median OS was only 16 months (CI 11-21) and 3-year OS was 35.2 % (CI 22-48 %). Age and ASCT were significantly associated with better OS in univariate (p = 0.002 and p < 0.001) as well in multivariate analysis (p = 0.004, HR = 0.023 and p = 0.001, HR = 0.014). Rituximab treatment, ASCT, and age are independent prognostic factors for OS in the first-line treatment of PCNSL.
Gesehen am 04.06.2020